PENGEMBANGKAN “KETERAMPILAN MOTORIK KASAR MELALUI STIMULASI PERMAINAN ANGKLUNG” PADA SISWA-SISWI ANAK USIA DINI - Faisal Rachmat (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2018)
This study used classroom action research. The aim of this study is to determine andeveloped abilityof the children’sgross motoric by playing angklungs. The research subjects were children in group A & B Age 3-7 Years old of RA. Nurul Amin inTotal 23 children consisting of 9 Girls and14boys. Researchers used the method of action class research with observation and documentation to collect data. Analysis of the data used in this research is the analysis of descriptive and qualitative.The results Showed an developed ability of the students’ gross motoric at 90% based on the evaluation of the results on the first cycle and second cycle.It can be concluded that the implementation of learning by utilizing angklung game to developed children's gross motoric abilities can be implemented in the learning process